First Gut Microbiome Profiling of the Critically Endangered Tricolour Langur (Presbytis chrysomelas cruciger) and Vulnerable Silvery Langur (Trachypithecus cristatus) in Sarawak, Malaysia - Roberta Chaya Tawie, Tingga; Ahmad, Ampeng; Jack, Liam; Bilhan, Deli; Mohd Luqman, Anuar; Dayang Nuriza, Abang-Abdillah; Noraini, Johari; Mohd Ridwan, Abd Rahman; Badrul Munir, Md Zain (John Wiley & Sons Ltd., 2026)
DNA metabarcoding is used to explore the gut microbiome of Presbytis chrysomelas cruciger and Trachypithecus cristatus from the Jemoreng Protected Forest. Phylum Firmicutes, family Lachnospiraceae, and genus Shuttleworthia are suggested as the key microbiome components for both species. The microbiome was primarily composed of beneficial bacteria essential for food digestion.